Methodological Tools for the Implementation of Oil and Gas Projects on the arctic and Continental Shelf - S. E. Trofimov (Мир новой экономики, 2023)
The presented article considers the methodological tools for the practical implementation of offshore hydrocarbon projects from the perspective of the system-functional approach. The research analyzes the provisions of the concept of integrated field development in the context of the policy of import substitution in the Russian oil and gas industry. A number of directions of methodological tools application have been identified and distinguished: environmental, technological, transport, infrastructure (including construction and improvement of new supply routes). The article shows how the sustainable development of all segments of the oil and gas complex, the institutional platform on which they are based, and the introduction of the latest technologies —  all contribute to the integrated development of offshore hydrocarbon reserves.